Application of Parallel Computation in Numerical Simulation of Laser Propulsion - Zeng, Yao Yuan; Zhao, Wen Tao; Wang, Zheng Hua (Applied Mechanics and Materials, 2012)
As for the problem of numerical simulation oflaser propulsion of three dimensions and multi-sub domains, the domain decomposition strategy based on message passing mechanismis applied in this paper to realize parallelization. The cell-centered finite volume scheme is performed to solve Euler equation. A five-step Runge-Kutta scheme of explicit integral model is used for time advancement. The spatial discretization of inviscid fluid is estimated byhigh-order Godunov-type scheme. We test some different examples on a cluster system and the results show the smallest number of speedup is more than 5.19 when the degree of parallelism is 8. In a word, parallel computation is an inevitable choice to achieve the aim of accelerating the study of the mechanism of laser propulsion.